Transformation of the Meaning of Reog Cemandian Dance in the People of Cemandi Village - Apriliza, Addis Fadilah; Sinduwiatmo, Kukuh (Universitas Muhammadiyah Sidoarjo, 2024)
This study describes the form of changing the meaning of the Cemandi Reog Dance as a form of entertainment for the Cemandi Village Community. Transformation is a change from the old form to the new form. The factors of change in the Art of Reog Cemandi Dance in this writing use a descriptive qualitative method to obtain a general and comprehensive overview of the social situation being studied or the object of research. The Cemandi Reog Dance is a traditional performing art that is believed by the people in Cemandi village as a rejection of reinforcements during the colonial period which created elements of rituals, dance movements, and music. The methods used in collecting data for this study include observations, interviews, and descriptions of the collected documentation. The qualitative data analysis approach by producing data in the form of narrated words to describe the phenomena that are happening in the field, before and after the transformation. The changes in the art of Reog Cemandi Dance are influenced by the factors of globalization. In this change, the results of research that lead to changes in the Reog Cemandi Dance not only occur as a form of ritual, but also experience changes caused by changing times, changing community conditions, people's mindsets, and also the environment. This art is still presented as a means of entertainment without eliminating the identity of the indigenous people of the culture itself and also without leaving the existing rituals.